The Effects of Principals' Transformational Leadership Style and Teachers' Work Commitment on Teacher Performance in Public Junior High Schools in Banyuasin III District - Yanuar Fikri; Yasir Arafat; Nur Ahyani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aimed to analyze the effects of principals' transformational leadership style and teachers' work commitment on teacher performance in public junior high schools in Banyuasin III District. The study employed an explanatory quantitative approach with an ex post facto design. The population comprised 139 teachers from five public junior high schools, while the sample consisted of 103 teachers determined using the Slovin formula at a 5% margin of error and selected through proportional random sampling. Data were collected using Likert-scale questionnaires and documentation. The instruments included 29 valid items for transformational leadership style, 29 valid items for work commitment, and 30 valid items for teacher performance. The corresponding Cronbach's Alpha coefficients were 0.964, 0.961, and 0.966. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, t-tests, an F-test, and the coefficient of determination with SPSS version 26. The findings showed that transformational leadership style had a positive and significant effect on teacher performance (B = 0.371; beta = 0.405; t = 5.003; p < 0.001). Teachers' work commitment also had a positive and significant effect (B = 0.411; beta = 0.381; t = 4.706; p < 0.001). Simultaneously, both variables significantly affected teacher performance (F = 28.311; p < 0.001; R² = 0.362), with the regression equation Y = 36.960 + 0.371X₁ + 0.411X₂. These findings emphasize the importance of inspirational school leadership and the continuous strengthening of teachers' commitment.